ONLINE DIGITAL TRANSACTIONS AS A SOLUTION FOR NATIONAL ECONOMIC RECOVERY DURING THE COVID-19 PANDEMIC - Shofwan Anwar Abdul Rauf; Anis Malik Thoha (Jurnal Multidisipliner Bharasa, 2022)
The Covid-19 pandemic has impacted face-to-face restrictions, which from a financial perspective reduces cash transactions. Payment with a cashless payment method is currently the leading choice of the community. Digital transactions are one way to anticipate the spread of viruses. This article aims to find out the behavior of the public towards the Cashless Payment method in financial transactions. The study uses a qualitative phenomenological approach. Through qualitative approaches, it is found that people's behavior in digital transactions is more due to humanitarian reasons. The community considers that the Covid-19 pandemic is a shared responsibility for that there needs to be mutual care. New Normal in the view of society is a form of learning in the form of increasing concern for self, society, and God. The follow-up of the results of this study encourages authors to conduct further research using quantitative approaches through multiple regression analysis. Further investigation showed that the use of Cashless Payment affects increasing spending, where simultaneously the increase in expenditure is directly proportional to the rise in bills, consumerism of food via online, shopping for drugs and vitamins, and sharing behaviors (Jogo Tongo).